Pengaruh PENGARUH FASILITAS DAN HARGA TERHADAP MINAT KUNJUNGAN WISATAWAN PADA WISATA BINAR ALAM VIEW DI KABUPATEN GARUT: Fasilitas, Harga, Minat Kunjungan Wisawatan, Objek Wisata Binar Alam View - Suryana, Lazio Allesandro; Adiatma, Dani (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
Facilities and price are among the key factors that influence public interest in a tourist destination. This study aims to analyze the influence of facilities and price on tourists' visiting interest at Binar Alam View, a tourism destination in Garut Regency. The research employed a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 30 visitors at the site. The results showed that facilities had a positive and significant influence on visiting interest, while price did not have a significant effect. Simultaneously, both variables significantly influenced visiting interest with a coefficient of determination of 45.2%. These findings indicate that the quality of facilities is the primary factor affecting tourists' intention to visit, while price tends to be a secondary consideration as long as it is perceived as fair.